The EFFECT OF THE QUALITY OF Morus cathayana LEAVES AGAINST NUTRITION INDEX Bombyx mori L. - Masitta Tanjung (International Journal of Ecophysiology, 2020)
The effect of quality mulberry leaf Morus cathayana on nutrition index of silkworm Bombyx mori L. have been conducted . This research was Completely Randomized Design (CRD) by two treatments. The first treatment was mulberry plant that cultivated on soil with Urea, TSP and NPK fertilizers and the second was the plants were not fertilized l. Each treatment was replicate 20 times. The results showed that the addition of Urea, TSP and NPK fertilizer on mulberry has effect (p<0,05) on increasing of the growth rate (GR) of instar III, the consumption rate (CR) of instars III and V, and efficiency of conversion of ingested food (ECI) of instar III and V. In addition, approximate digestibility (AD) of instar III, IV were 20%, 7%, 24%, 40% and then V was 51%, 15%, 21% and 70% respectively.